Neurons generated by direct conversion of fibroblasts reproduce synaptic phenotype caused by autism-associated neuroligin-3 mutation - Chanda, Soham (National Academy of Sciences, 2013)
Recent studies suggest that induced neuronal (iN) cells that are directly transdifferentiated from nonneuronal cells provide a powerful opportunity to examine neuropsychiatric diseases. However, the validity of using this approach to examine disease-specific changes has not been demonstrated. Here, we analyze the phenotypes of iN cells that were derived from murine embryonic fibroblasts cultured from littermate wild-type and mutant mice carrying the autism-associated R704C substitution in neuroligin-3. We show that neuroligin-3 R704C-mutant iN cells exhibit a large and selective decrease in AMPA-type glutamate receptor-mediated synaptic transmission without changes in NMDA-type glutamate receptor- or in GABA(A) receptor-mediated synaptic transmission. Thus, the synaptic phenotype observed in R704C-mutant iN cells replicates the previously observed phenotype of R704C-mutant neurons. Our data show that the effect of the R704C mutation is applicable even to neurons transdifferentiated from fibroblasts and constitute a proof-of-concept demonstration that iN cells can be used for cellular disease modeling.